2011
DOI: 10.1080/10888438.2010.528480
|View full text |Cite
|
Sign up to set email alerts
|

Spelling of Deaf Children Who Use Cochlear Implants

Abstract: The spellings of 39 profoundly deaf users of cochlear implants, aged 6 to 12 years, were compared with those of 39 hearing peers. When controlled for age and reading ability, the error rates of the 2 groups were not significantly different. Both groups evinced phonological spelling strategies, performing better on words with more typical sound-spelling correspondences and often making misspellings that were phonologically plausible. However, the magnitude of these phonological effects was smaller for the deaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
2
28
1
Order By: Relevance
“…Nearly three quarters of spelling errors for the hearing dyslexic group were phonologically plausible, compared with just over half the errors of the oral deaf group; percentages which are very much in line with previous findings for hearing dyslexic and oral deaf children of this age (Hayes et al, 2011;Plisson et al, 2013). Bearing in mind that our hearing dyslexic group were younger, and that PPE increases with age, it is likely that this is a conservative estimate of the overall differences in spelling strategies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nearly three quarters of spelling errors for the hearing dyslexic group were phonologically plausible, compared with just over half the errors of the oral deaf group; percentages which are very much in line with previous findings for hearing dyslexic and oral deaf children of this age (Hayes et al, 2011;Plisson et al, 2013). Bearing in mind that our hearing dyslexic group were younger, and that PPE increases with age, it is likely that this is a conservative estimate of the overall differences in spelling strategies.…”
Section: Discussionsupporting
confidence: 74%
“…However, there were individual differences; some late exposure CS children with better speech intelligibility had phonological error scores within the confidence limits of the hearing controls. Hayes, Kessler, and Treiman (2011) study of 39 profoundly deaf English speaking children with cochlear implants, 6-12 years, mean age 8.97 years, found their spelling was less accurate compared with CA hearing children, but did not differ after controlling for reading differences. However, a higher proportion of the spelling errors of the hearing group were phonologically plausible (75% vs. 44% deaf children with CI), a difference that was not accounted for by differences in reading levels.…”
mentioning
confidence: 94%
“…Children with cochlear implants spelled on average 85.75 per cent of words in their written stories correctly, which is higher than Hayes et al (2011) reported in familiar dictated single words (55 per cent). Similarly, Werfel and Krimm (2013) reported that children with normal hearing were more accurate at spelling words in stories than dictated single words, presumably because children can select words to use in written stories.…”
Section: Discussionmentioning
confidence: 60%
“…On such measures, Hayes et al (2011) reported that school-age children with cochlear implants spelled only 55 per cent of words correctly, compared to 66 per cent by their same-age peers (d = .41). Likewise, Apel and Masterson (2015) reported that school-age children with cochlear implants spelled substantially fewer words correctly than reading-level-matched children with normal hearing (d = 1.01).…”
mentioning
confidence: 96%
“…At this stage, they must use their WM resources also for higher level writing processes, like organizing their ideas in a logical text structure. [28,29] Children with CIs, and deaf children more in general, can encounter problems at all these levels, that is in transcription [30][31][32][33][34] text generation (e.g. [14,16]), and in planning and text monitoring.…”
Section: The Written Production Of Children With Cismentioning
confidence: 99%